Pembuatan Building Blocks Dengan Mesin” CREATICS” Menggunakan Metode Design Thinking - Jayakusuma, Aria Prima; Parwati, Niken; Tanjung, Widya Nurcahayanty; Purwandari, Aprilia Tri (Universitas Al Azhar Indonesia, 2022)
This research was conducted to help solve the problem of environmental pollution resulting from excessive use of plastik and the use of wood as a raw material for production. In addition, the development of creatics 2.0 products to create new products that are of interest to consumers. In this study, the manufacture of product types will be made based on a questionnaire given to 30 respondents to provide input regarding the type and reasons for making the product, which is then concluded to be a decision for the final product to be made. After knowing the type of product to be produced, the design thinking method is used to collect the wishes and opinions of users regarding similar products to find out consumer needs. Design thinking goes through 5 stages of the work process, namely empathize, define, ideate, prototype, and test. The design thinking process is a product development process that prioritizes consumer needs. And from data collection and processing, it can be concluded that the desired product is a furniture product that is flexible, lightweight, waterproof, strong, weather-resistant, and easy to store. In addition, plastik molds are also needed in the manufacturing process, the required mold specifications are plastik molds that can be integrated with the creatics machine so there is no need for refutation, and plastik molds that can withstand the heat of the melted plastik until the molding process is complete.Keywords – Product development, Plastik recycle, Design thinking